PENGARUH E-COMMERCE, MEDIA SOSIAL, SISTEM INFORMASI AKUNTANSI, DAN EKSPEKTASI PENDAPATAN TERHADAP PENGAMBILAN KEPUTUSAN BERWIRAUSAHA MAHASISWA JURUSAN AKUNTANSI UPN VETERAN JAWA TIMUR - Jessica Margareta; Anik Yuliati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the influence of E-Commerce, social media, Accounting Information Systems, and Income Expectations on the entrepreneurial decision-making of accounting students at UPN Veteran East Java. Using a quantitative approach, data were collected from students through structured questionnaires and analyzed using multiple regression techniques. The results reveal that all four variables—E-Commerce, social media, Accounting Information Systems, and Income Expectations—have a significant positive effect on students' entrepreneurial decision-making. E-Commerce was found to be the most dominant factor, highlighting the crucial role of digital platforms in shaping students’ readiness and motivation to start their own businesses. Social media contributes by providing access to market trends and networking opportunities, while Accounting Information Systems support better financial management and decision-making. Additionally, Income Expectations serve as a motivating factor, encouraging students to pursue entrepreneurship as a viable career path. These findings suggest that integrating technology and financial awareness in entrepreneurship education can effectively enhance students’ ability to make informed entrepreneurial decisions. This study provides valuable insights for educational institutions aiming to foster entrepreneurship among accounting students in the digital era.